24.4k views
3 votes
How to simplify the fractions

How to simplify the fractions-example-1
User Easeout
by
5.2k points

1 Answer

5 votes

Answer:


\large\boxed{(3x+6)/(x-4)/(2x^2+9x+10)/(x^2+4x)=(3x(x+4))/((x-4)(2x+5))}

Explanation:

Just like that


(3x+6)/(x-4)/(2x^2+9x+10)/(x^2+4x)=(3x+6)/(x-4)\cdot(x^2+4x)/(2x^2+9x+10)\\\\=(3(x+2))/((x-4))\cdot(x(x+4))/(2x^2+4x+5x+10)=(3(x+2))/((x-4))\cdot(x(x+4))/(2x(x+2)+5(x+2))\\\\=(3(x+2))/((x-4))\cdot(x(x+4))/((x+2)(2x+5))\qquad\text{cancel}\ (x+2)\\\\=(3x(x+4))/((x-4)(2x+5))

User Frement
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.